Comparing the three color pounehh tooth paste with the conventional one in preventing the formation of the microbial plaque - Ebadifar A.; Naghibi A.; Valaie N.; Ramezani GH; Sadat Mansori S. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: Plaque control has always been important in preventive dentistry. Various methods and materials have been introduced for this purpose. Recently a three-colored tooth paste has been introduced which claims to prevent plaque formation. The aim of this study was to compare three-colored pouneh tooth paste containing triclosan with the conventional one in preventing plaque formation. "nMaterials and Methods: This was a randomized double blind cross over clinical trial which was carried out on 40 dental students of Tehran azad university in 2005. Before beginning the trial, the index of plaque was evaluated, registered and reduced to null. The subjects were randomly divided into two groups, the case group (three color tooth paste) and the control group (conventional tooth paste). The participants were asked to apply the specified tooth paste with an oral B Advantage Artica toothbrush for two weeks. After two weeks, the amount of plaque was re-registered and again reduced to null. The type of tooth paste was changed among two groups and the plaque was registered for the third time at the end of two weeks. Then the patients and assessors were not aware of the type of tooth paste in the tubes (double blind). McNamar and ManWhitney test were used. "nResults: From the 40 subjects, 4 cases were omitted due to the different reasons. The amount of initial plaque index was 88.3 12.1 which was reduced to 78.2 16.9 in the control and 74.1 19.3 in the case group. The difference between primary plaque and secondary plaque (after applying tooth paste) was significant in both case and control groups, however there was not any significant difference between two groups. "nConclusion: Based on the results of this study, there was not any significant difference between conventional and three-colored tooth paste in reducing the plaque index.